The effect of vitamin D supplementation in third-trimester pregnant women on early infant growth: an experimental study - Zaenudin Zaenudin; Suci Saftari Apriani; Soffa Abdillah (Jurnal Gizi Klinik Indonesia, 2026)
Background: Vitamin D deficiency among pregnant women remains a public health concern and may contribute to impaired intrauterine growth and an increased risk of stunting in early life. However, evidence regarding the effect of vitamin D supplementation on early infant growth indicators remains limited, particularly in primary healthcare settings.Objective: This study aimed to analyze the association between vitamin D supplementation during pregnancy and early infant growth indicators.Methods: A total of 95 participants were included in the analysis, consisting of 47 pregnant women in the intervention group and 48 in the control group. Baseline assessments included demographic characteristics, third-trimester maternal body mass index, and serum 25-hydroxyvitamin D [25(OH)D] levels. Early infant growth parameters included birth weight, birth length, and head circumference at birth. Statistical analyses were performed using the Mann–Whitney test and multiple linear regression.Results: Vitamin D deficiency was identified in 87.37% of pregnant women. Infants in the intervention group had higher mean birth weight (3.22 ± 0.31 kg vs 2.75 ± 0.47 kg), birth length (50.55 ± 1.72 cm vs 48.15 ± 1.68 cm), and head circumference (32.65 ± 1.22 cm vs 29.70 ± 1.72 cm) compared with the control group (all p < 0.001). Multivariate analysis demonstrated that birth length and head circumference were significantly associated with infant growth outcomes, with head circumference emerging as the most dominant predictor (β = 0.612). In contrast, birth weight was not significantly associated with the outcome after adjustment for other variables.Conclusion: Vitamin D supplementation during pregnancy was associated with improved linear growth and larger head circumference at birth, highlighting the importance of maternal vitamin D status in supporting optimal infant growth from the prenatal period.